2012
DOI: 10.1159/000332220
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Salvage Cryotherapy for Radiorecurrent Prostate Cancer: A Centre’s Experience

Abstract: Introduction: The experience of a tertiary centre in the management of recurrent prostate cancer after radiotherapy by salvage cryotherapy is presented. Patients and Methods: Between February 2006 and August 2008, 19 patients underwent salvage cryotherapy for radiorecurrent prostate cancer. Post-radiotherapy recurrence was confirmed by prostatic biopsy. The ‘Phoenix definition’ was used to define biochemical failure after salvage cryotherapy. Results: The mean age at cryotherapy was 69.2 years and the mean tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…Only 1.5% of patients in the entire cohort in this analysis developed fistulas. This is consistent with previous published morbidity data [8,9,15,18]. Two of the six patients that developed a fistula had undergone lowdose-rate brachytherapy as primary treatment, followed by two subsequent SCs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Only 1.5% of patients in the entire cohort in this analysis developed fistulas. This is consistent with previous published morbidity data [8,9,15,18]. Two of the six patients that developed a fistula had undergone lowdose-rate brachytherapy as primary treatment, followed by two subsequent SCs.…”
Section: Discussionsupporting
confidence: 92%
“…Median primary and secondary adapted Gleason score and Gleason sum after RT (as interpretation of Gleason grading after RT is limited) were significantly less favourable in patients who died overall, as compared to patients that were still alive at last follow-up (4 [3][4][5] [6][7][8][9][10]; p < 0.01), a finding that could not be shown for patients who died of disease, or whose disease recurred. This result was also reflected in univariate analyses, where higher adapted Gleason score and Gleason sum were significantly associated with worse OS ( p < 0.01).…”
Section: Predictors Of Outcomementioning
confidence: 86%
See 1 more Smart Citation
“…Data from our institution have shown a DFS rate at 10 years of between 39 and 64% with presalvage PSA <5 ng/ml and presalvage Gleason score ≤7 being the best predictor of disease-free recurrence at 10 years [32]. Recently, Philippou et al [33] have reported a DFS rate at 2 years of 58% with a median PSA nadir of 0.20 ng/ml. A summary of available studies is included in table 3.…”
Section: Cryotherapymentioning
confidence: 99%
“…With improvements in CRYO devices and techniques, the incidence of complications has decreased with time. Urinary incontinence rates ranging from 10.5 to 36% [21,33] in comparison to incontinence rates of 41% reported in salvage RP, whilst the fistula rates were from 2.6 to 5.3% [22,33], have been reported with CRYO in comparison with rectal injury rates from 2 to 15% with salvage RP. The risk of complications seems to be higher in the presence of prior transurethral surgery.…”
Section: Cryotherapymentioning
confidence: 99%